PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SIMULASI DAN KOMUNIKASI DIGITAL KELAS X MULTIMEDIA DI SMK SUMBER BUNGA - Sitti Tolak Nurlaila (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2022)
Without interest in learning from students, the learning process will not take place optimally and learning outcomes will not be satisfactory. This can be seen from the lack of interest in learning and the lack of activity in learning activities, as a result the learning process becomes less effective. The purpose of this study was to determine whether or not there was an effect of the Contextual Teaching and Learning (CTL) learning model on students' interest in learning in Simulation and Digital Communication lessons at Sumber Bunga Vocational School. This research uses quantitative methods. The approach used is ex post facto research. The sampling technique used purposive sampling, namely 34 students of class X Multimedia at SMK Sumber Bunga. Data collection techniques used are observation, interviews, questionnaires, and documentation. Data analysis used normality test, validity test, reliability test, correlation test and t test. The results of the t test are known that the value of tcount = 2.875 while the value of ttable = 2.032 means tcount> ttable. Thus, it can be concluded that there is an effect of the CTL learning model on students' interest in learning in the subjects of Simulation and Digital Communication class X Multimedia at SMK Sumber Bunga with a moderate level of influence.